2004
DOI: 10.1638/03-106
|View full text |Cite
|
Sign up to set email alerts
|

Transitional Cell Carcinomas in Four Fishing Cats (Prionailurus Viverrinus)

Abstract: Transitional cell carcinomas (TCC) of the urinary bladder were diagnosed in four related fishing cats (Prionailurus viverrinus). The major clinical sign in each case was persistent hematuria unresponsive to medical therapy. Cystotomy and biopsy provided an antemortem diagnosis in three of the fishing cats before euthanasia because of progression of clinical signs. The diagnosis was made in the fourth cat after euthanasia because of renal failure. Hematuria improved temporarily in one of the cats diagnosed ante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 9 publications
5
28
1
Order By: Relevance
“…Although infrequent, metastastatic infiltration of urinary bladder TCC to the lumbar vertebra results in spinal cord compression, leading to clinical signs such as hindlimb paralysis (De Moura et al 2007), as observed in the oncelot of the present report. Hematuria is the most common clinical sign of bladder neoplasia in dogs and cats with TCC (Sutherland-Smith et al 2004), however was not observed this or other urinary signal in the present study.…”
Section: Resultscontrasting
confidence: 73%
See 1 more Smart Citation
“…Although infrequent, metastastatic infiltration of urinary bladder TCC to the lumbar vertebra results in spinal cord compression, leading to clinical signs such as hindlimb paralysis (De Moura et al 2007), as observed in the oncelot of the present report. Hematuria is the most common clinical sign of bladder neoplasia in dogs and cats with TCC (Sutherland-Smith et al 2004), however was not observed this or other urinary signal in the present study.…”
Section: Resultscontrasting
confidence: 73%
“…In wild felines rare cases were described; all cases in small wild felines. Four cases of urinary bladder neoplasia was described the fishing cats (Prionailurus viverrinus) (Sutherland-Smith et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…3,12,13 The pulmonary nodule detected during the initial examination of the cat described in the present report was a small solitary lesion, and results of histologic examination indicated that it was unrelated to the urinary bladder tumor. 3,12,13 The pulmonary nodule detected during the initial examination of the cat described in the present report was a small solitary lesion, and results of histologic examination indicated that it was unrelated to the urinary bladder tumor.…”
Section: Discussionmentioning
confidence: 49%
“…Captive fishing cats have a high incidence of transitional cell carcinomas (TCC) (Sutherland-Smith et al, 2004). Mean age in affected cats is 10.8 years and no sex predilection has been noted.…”
Section: Common Neoplasms In Felidsmentioning
confidence: 99%